VIRTUAL PLATFORM FOR PASSING LABORATORY CLASSES IN COMPUT - Madyarova, G.A.; Aubakirov, T.M. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article analyzed platforms for conducting online laboratory classes, which led to the proposal of a virtual learning platform as a solution for creating a learning environment. Modern distance learning platforms combined with pedagogical technologies provide the convenience of learning through online tasks in the process of meeting the requirements of students. Based on the identified results, video tutorials, tasks, and theory were proposed in order to improve educational achievements. The analysis revealed the absence of platforms for conducting online laboratory classes in the Kazakh language. Based on these studies, the content and structure of the online learning environment for passing laboratory classes in computer science in the 7th grade of secondary school based on the textbook computer science is determined. The platform for conducting online laboratory classes was created using wordpress and additional plugins.